Assessment of the health of the Swan-Canning river system using biochemical markers of exposure of fish - Webb, Diane (Curtin University, 2005)
Most environmental studies concerning the environmental health of the Swan- Canning River system have focussed on nutrient inputs from both rural and urban catchments that are the cause of algal blooms. On occasions these algal blooms have resulted in fish deaths attributed to oxygen starvation. Relatively few studies have examined whether non-nutrient contamination is affecting the health of the riverine environment. Those studies that have, have concentrated on measuring the levels of heavy metals, organochlorines, organophosphates, and hydrocarbons in the sediments and water of the river system, and in the flesh of the biota. However, chemical analysis often fails to detect chemicals of concern due to high laboratory detection limits. In addition, analysis of the body burden of contaminants within biota does not necessarily convey if exposure is inducing adverse effects at the individual or ecosystem levels. The use of biochemical markers as a tool for the assessment of the health of the Swan-Canning River system was examined under a collaborative research project with the Waters and Rivers Commission, established in response to the recognition of the paucity of information from chemical analyses. The present study focussed on the estuarine portion of the Swan-Canning River system, using the black bream (Acanthopagrus butcheri), an estuarine dependent fish species, as a biomonitoring tool. Prior to the commencement of this study it had been determined that the black bream was a suitable fish species for use as a biomonitoring tool when using mixed function oxygenase (MFO) activity induction under laboratory conditions.Biopsies taken from feral black bream collected from eight sites during the period 2000 to 2002 from the estuary confirmed that the use of MFO induction in this fish species as a biomarker of exposure to organic contaminants is a reliable biomarker. Fish gender was a confounding factor in the interpretation of MFO induction when using the enzyme ethoxyresorufin-O-deethylase (EROD) as EROD activity was suppressed in both pre- and post-spawning female black bream. No such suppression was identified when using the MFO enzyme ethoxycoumarin-O-deethylase (ECOD). However, due to differences in the pattern and intensity of the induction of EROD and ECOD activities it was concluded that ECOD activity was not a substitute for EROD activity to detect certain chemical as ECOD activity represents a different cytochrome P450 pattern to EROD activity. No spatial, seasonal or interannual differences in the level of the enzyme sorbitol dehydrogenase (SDH) in the blood of the black bream were measured indicating that the interpretation of MFO activity induction was not compromised by hepatocellular damage. This study has shown that the black bream in the Swan-Canning Estuary are exposed to, and are metabolising polycyclic aromatic hydrocarbons (PAHs), notwithstanding that the chemical analysis of the contaminant load of these substances in the estuarine waters is consistently below laboratory detection limits. In addition, biomarker responses such as ECOD activity indicate that various other organic pollutants are present and are being metabolised by the black bream.The measurement of biliary metabolites clearly show that, under winter conditions, the comprehensive drainage system of the Swan Coastal Plain contributes PAHs from pyrogenic sources such as burnt fuels into the estuary although the onset and intensity of rainfall events notably impacts on the volume of stormwater inflow. During the summer months, when freshwater flow is minimal, petrogenic sources of PAHs are dominant. Metabolic enzyme analysis points to the black bream being challenged in their aerobic capacities during summer, and that gill tissue was the most suitable tissue to evaluate the aerobic and anaerobic capacity of this fish species. Furthermore, there was a significant negative correlation between stress protein (hsp70) expression and DNA integrity in field-collected fish suggesting that the black bream within the estuary are highly stressed. No gradient of response in biomarker levels was identified in the Swan-Canning Estuary under either winter or summer conditions indicating there are multiple sources of inputs of potential pollutants along the length of the estuary. Stormwater and road runoff are the primary source of pollutant input into the estuary in the winter months, while summer biomarker levels, particularly PAH, appear to reflect the high usage of the estuary for recreational purposes and runoff from poorly irrigated parks and gardens. Significant rainfall events at any time of the year have the potential to adversely impact the biota of the estuary, particularly when these events result in a flush of water from the drains following long dry periods.The study shows that the black bream is a suitable fish species to use under field conditions to detect the presence of bioavailable non-nutrient contamination within the Swan-Canning Estuary. A suite of biomarkers in black bream have been tested seasonally and annually but only a small number of biomarkers have proven suitable for routine monitoring of the health of the Swan-Canning Estuary. This treatise concludes with several recommendations for further investigations into biomarkers of fish health for the purpose of increasing our understanding on the sources and type of contamination entering the estuary, and potential effects on the aquatic biota of the Swan-Canning River system. These recommendations include, but are not limited to: (1) the need to determine baseline levels for the different biomarkers investigated in this study, (2) the examination of the Moore River or the Warren River estuaries as potential reference sites for biomarker studies in the Swan- Canning Estuary, (3) the advantage of identifying a second estuarine-dependent indigenous fish as a biomonitoring tool, (4) the requirement for a targeted study aimed at clarifying the relationship between major drain discharges, biomarker levels and impacts on river biota, and (5) a study of estuarine waters utilising SPMDs be undertaken in tandem with biomarker analysis of field captured fish would be beneficial.